2018
DOI: 10.3389/fmicb.2017.02638
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic and Bactericidal Properties of Channel Catfish Peritoneal Macrophages Exposed to Edwardsiella ictaluri Live Attenuated Vaccine and Wild-Type Strains

Abstract: Edwardsiella ictaluri (E. ictaluri), a Gram-negative, intracellular, facultative bacterium, is the causative agent of enteric septicemia of catfish (ESC), which is one of the most significant diseases of farmed channel catfish. Macrophages have a critical role in major defense mechanisms against bacterial infections by migrating to the site of infection, engulfing and killing pathogens, and priming adaptive immune responses. Vaccination of catfish with E. ictaluri live attenuated vaccine (LAV) strains increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 87 publications
7
18
0
Order By: Relevance
“…The phagocytic cells are functioned in stimulating an inflammatory response, phagocytosis and bactericidal action and nitric oxide (NO) for killed pathogens. In the current study, the phagocytosis activity in vaccinated fish was higher both before and after infection with S. iniae and A. hydrophila compared with the unvaccinated fish, which was similar to record by Kordon [51]. Additionally, similar results have been also shown in vaccinated striped catfish (Pangasianodon hypophthalmus) those were immunised with A. hydrophila [49].…”
Section: Discussionsupporting
confidence: 91%
“…The phagocytic cells are functioned in stimulating an inflammatory response, phagocytosis and bactericidal action and nitric oxide (NO) for killed pathogens. In the current study, the phagocytosis activity in vaccinated fish was higher both before and after infection with S. iniae and A. hydrophila compared with the unvaccinated fish, which was similar to record by Kordon [51]. Additionally, similar results have been also shown in vaccinated striped catfish (Pangasianodon hypophthalmus) those were immunised with A. hydrophila [49].…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that deletion of evpB of T6SS caused nearly complete loss of E. ictaluri virulence in catfish and EievpB provided good protection against EiWT infection (Abdelhamed, Lawrence, & Karsi, 2018). EievpB also showed high-internalisation rate in catfish peritoneal macrophages (Kordon et al, 2018). In this study, removal of evpP caused numerical but not statistically significant virulence attenuation in catfish, and the internalisation rate of EiΔevpP in catfish peritoneal macrophages was similar to that of EiWT.…”
Section: Discussionsupporting
confidence: 49%
“…Bacterial killing and cytospin were performed as previously described (Booth, Beekman, & Thune, 2009;Kordon et al, 2018;Russo, Shoemaker, Panangala, & Klesius, 2009 Peritoneal macrophages were incubated with EiΔevpP and EiWT at 32°C for 2 hr. Then, cells were harvested and washed, and the cytospin slides were prepared by using a Cyto-Tek cytocentrifuge (Sakura) set at 160 g (500 rpm) for 1 min.…”
Section: Macrophage Killing Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were examined under fluorescence microscopy. For flow cytometry, the phagocytosis to BCG-p was performed as previously report [41]. Briefly, THP-1 cells were infected by GFP-expressing BCG-p for 4 h, then the cells were rinsed with PBS, next the cells were removed form plates and were measured with BD Accuri C6.…”
Section: Phagocytosis Assaymentioning
confidence: 99%